Advances in macrophage-myofibroblast transformation in fibrotic diseases - Ban, Jia-Qi; Ao, Li-Hong; He, Xiu; Zhao, Hua; Li, Jun (Frontiers in Immunology, 2024)
Abstract: Macrophage-myofibroblast transformation (MMT) has emerged as a discovery in the field of fibrotic disease research. MMT is the process by which macrophages differentiate into myofibroblasts, leading to organ fibrosis following organ damage and playing an important role in fibrosis formation and progression. Recently, many new advances have been made in studying the mechanisms of MMT occurrence in fibrotic diseases. This article reviews some critical recent findings on MMT, including the origin of MMT in myofibroblasts, the specific mechanisms by which MMT develops, and the mechanisms and effects of MMT in the kidneys, lungs, heart, retina, and other fibrosis. By summarizing the latest research related to MMT, this paper provides a theoretical basis for elucidating the mechanisms of fibrosis in various organs and developing effective therapeutic targets for fibrotic diseases.